Caracterização dos constituintes voláteis de espécies do gênero de Sparattanthelium Mart. (Hernandiaceae) e avaliação de fitotoxicidade e citotoxicidade em plantas modelo - Dutra, Quezia Pains (2019)
Brazil has been prominent in the production of agrochemicals; however, its use in agriculture has related to the environment and other organisms. The plants are reservoirs of secondary metabolites and may present allelopathic effect, being interesting to be used as bioherbicides. These metabolites can be found in essential oils in basal angiosperms. They have been found to be economically useful, such as groups are used for medicinal purposes and have shown antiproliferative activity in cancerous and antimicrobial cells. However, some species have unknown allelopathic and bioherbicidal potential, such as the genus Sparattanthelium, exclusively neotropical. Few species of this genus have been chemically characterized and the biological potential of the compounds is not known. The objective of this work was to evaluate the effect of the essential oils extracted from the leaves of Sparattanthelium botocudorum and Sparattanthelium tupiquinorum in bioassays with the species Lactuca sativa and Sorghum bicolor. The oils were tested at concentrations of 3000, 1500, 750, 375 and 187.5 ppm. The chemical characterization was performed and the percentage of germinated seeds, the initial development of Lactuca sativa L. and Sorghum bicolor L. seedlings and the changes in the meristematic cycle of L. sativa roots. The major compound of both species was germacrene D (33.2 and 44.8%), followed by bicyclogermacrene (23.4 and 16.9%), ß-element (8.4 and 5.1%), germacrene A (17.7 and 8.7%). Tras-nerolidol (7.7%) was found only in S. botocudorum and ?-Cadinene (15%) in S. tupiquinorum. The phytotoxic assay revealed that the essential oil of both species reduced the root and aerial growth of L. sativa seeds. In S. bicolor it reduced germination and aerial growth. In the cytotoxic assay, the mitotic index and the increase of chromosomal and nuclear alterations resulting from the aneugenic and clastogenic action of the essential oils of S. botocudorum and S. tupiquinorum were observed.